Evaluasi Penerapan Sistem Informasi Manajemen Puskesmas (Simpus) dengan Model Human, Organization, Technology (Hot) – Net Benefit (Fit) di Puskesmas Tambun Bekasi Tahun 2022 - Salma Karami Andrea Puspa; Evindiyah Prita Dewi; Umniyatun, Yuyun (Jurnal Kesehatan Komunitas, 2023)
The Health Center Information System (SIMPUS) is a system for recording and reporting health activities at the Health Center which is currently being carried out mostly electronically (e-Puskesmas). BPJS as the organizer of national health insurance has prepared an information system, namely P-Care for recording JKN patients at the Puskesmas so that the two systems are integrated. HOT-Fit is a framework that can be used to evaluate information systems. This model positions the important components in information systems, such as people, organizations, and technology, as well as the relevant relationships between these components. This study aims to evaluate the application of e-Puskesmas and P-Care information systems with the Human Organization Technology (HOT)-Fit model at the Tambun Bekasi Health Center. This research is a descriptive study using a qualitative approach with in-depth interviews, observation, and documentation studies. The results of the study show that from the aspect of the human component training is still needed to improve the knowledge and skills of officers, the organizational aspect has built an appropriate organizational structure and the working officers are by their competencies and the necessary facilities and infrastructure are complete. In terms of technology, it is known that system quality, information quality, and service quality have been well achieved. The information system that has been running well in the Puskesmas studied is an example of good recording and reporting management so that it can be used as a benchmark for other Puskesmas. A well-managed information system can assist the decision-making process for Puskesmas management to achieve its main goals.